Analyzing Indonesia’s NCICD Project to Stop the Capital City Sinking - Aris Widodo (Otoritas : Jurnal Ilmu Pemerintahan, 2017)
Jakarta is hit by a tidal flood every year and cause some loss for the city. Beside that flood caused by sea level rise, the city risk on sinking is higher because of land subsidence problem. Without any significant action, it is predicted that Jakarta will face USD 521 million loss risks on 2050 caused by flood. To overcome the sinking problem, Indonesian government plays an active role on the international action to combat climate change. In addition, Indonesian government also implements NCICD project, in which create giant sea wall and land reclamation on the Jakarta Bay.  However, the land reclamation raises an argument that it would create an environment disaster for the city. Because of that, it is suggested that Jakarta should only create a sea wall without land reclamation. Moreover, Jakarta government also should ensure that Spatial City Planning and New Rule on ground water extraction are well implemented so the land subsidence in the city is stopped.